Biquads Based on Single Negative Impedance Converter Implemented by Classical Current Conveyor - Dostal, Tomas; Axman, Vladimir (Radioengineering Society, 2007)
The paper deals with continuous-time ARC biquadratic (second-order) filters based on the single classical three-port current conveyors, so called second generation CC II. A unique application of the CC II is discussed, when the terminals Y and Z are connected together. Using this way a negative impedance converter is obtained as a suitable building block in synthesis of several biquads, including notch filters.
Keywords: Analogue circuits; active RC filters; biquads; current conveyors; negative impedance converters